Application of Duplex Polymerase Chain Reaction and Whole Genome Sequencing in Analyzing Carbapenem Resistance Genes in Clinical Klebsiella pneumoniae Isolates - Giang, Phan Thi Chau; Anh, Nguyen Phuong; Anh, Pham Thi Mai; Nhat, Truong My; Hoai, Nguyen Thi Thu (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 4, 2025)
Klebsiella pneumoniae ( K. pneumoniae ) is a Gram-negative, encapsulated bacterium with the potential for high virulence and antibiotic resistance. Its ability to develop multidrug resistance poses a global threat, particularly in clinical settings. The study aimed to compare the application of two different molecular-based methods, duplex polymerase chain reaction (PCR) and whole genome sequencing (WGS), to investigate the prevalence of carbapenem resistance genes, including bla KPC , bla NDM , bla VIM , and bla OXA-48 in 41 K. pneumoniae isolates from intensive care units. As a result, both methods showed the absence of bla VIM in all isolates. Interestingly, K. pneumoniae carbapenemase (KPC) was revealed to be the least common carbapenemase type despite the previously reported prevalence of KPC-producing Enterobacterales. There was no difference between the two methods in yielding the high prevalence of bla OXA -carrying K. pneumoniae strains, which is consistent with global trends. In detail, while PCR detected the presence of the oxacillinase (OXA) 48 gene well, WGS did not. In contrast, WGS revealed the presence of OXA-48-like variant, OXA-181. Notably, regarding the co-occurrence of carbapenemase types, the PCR method identified two isolates carrying all three types, while WGS analysis did not report this. In conclusion, PCR and WGS have advantages and limitations in detecting antibiotic resistance genes. PCR is efficient and straightforward but unable to detect all gene variations. On the other hand, WGS is more resource-intensive but can provide comprehensive variant information, which is important regarding the diversity of antibiotic-resistance genes.